2022
DOI: 10.1002/gps.5711
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders and risk of subsequent dementia: Systematic review and meta‐analysis of longitudinal studies

Abstract: Objectives Although psychiatric disorders have been found to be associated with increased risk of dementia, previous findings are mixed, and the nature of these relationships remains poorly understood. We examined longitudinal associations between depression, anxiety, post‐traumatic stress disorders (PTSD), bipolar disorder (BPD), psychotic disorders and subsequent dementia. Methods We searched three databases for longitudinal, population‐based studies investigating associations between psychiatric disorders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 85 publications
6
34
0
1
Order By: Relevance
“…In addition to epilepsy, ASMs are commonly prescribed to treat bipolar disorder, depression, and other mental disorders ( 6 ). Previous meta-analysis have demonstrated that bipolar disorder is associated with an increased risk of dementia ( 30 ). Three included studies ( 11 , 12 , 17 ) focused on patients with bipolar disorder and used non-exposed patients as negative controls to minimize the effects of indication.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to epilepsy, ASMs are commonly prescribed to treat bipolar disorder, depression, and other mental disorders ( 6 ). Previous meta-analysis have demonstrated that bipolar disorder is associated with an increased risk of dementia ( 30 ). Three included studies ( 11 , 12 , 17 ) focused on patients with bipolar disorder and used non-exposed patients as negative controls to minimize the effects of indication.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent data (2019) was used for the current study. Though there is significant evidence for an association between MDD and both Parkinson's and Alzheimer's disease [37][38][39], dysthymia was also included in the analysis in view of older data suggesting that it may be associated with both these disorders [86]. Data on the estimated prevalence of Parkinson's disease, and of Alzheimer's and related dementias, was obtained from the same source.…”
Section: Methodsmentioning
confidence: 99%
“…In a study of patients with severe depression and no signs of parkinsonism, 6.5% of patients developed Parkinson's disease when followed up over 9 years [37], and a meta-analysis of eleven studies found that, regardless of age, a diagnosis of depression was associated with at least a two-fold increase in the risk of subsequent Parkinsonism; these results remained significant even after adjusting for potential confounders [38]. Likewise, a meta-analysis of longitudinal studies found a significant association between depression and the subsequent risk of Alzheimer's disease, with stronger effects noted for severe-or late-life depression [39], and a review of six meta-analyses found that syndromal depression was associated with a 1.5-fold increase in rates of subsequent Alzheimer's disease [40]. The exact mechanism underlying these associations is unknown, but various mechanisms have been suggested to account for this link.…”
Section: Introductionmentioning
confidence: 95%
“…Der Zusammenhang zwischen dem Bestehen nicht dementieller psychiatrischer Erkrankungen in der Jugend bis ins mittlere Erwachsenenalter und der Entwicklung einer Demenz im Alter ist nachgewiesen. Daher ist es von großer Bedeutung, dass zu hoher Bildschirmmedienkonsum das Risiko von psychischen Störungen wie Depression einschließlich Suizidalität 2 , 56 , 57 , Angst 4 , 25 , 31 und Sucht (sowohl stoffgebundene als auch nicht stoffgebundene Suchterkrankungen, d. h. Alkohol, Nikotin und Drogen als auch Medien, Computerspiele, Smartphones und Facebook 9 , 17 , 19 erhöht, die als Risikofaktoren für Demenz bekannt sind 21 , 51 , 63 . Betrachten wir einige Beispiele etwas genauer.…”
Section: Psychische Störungen In Jüngeren Jahren Können Zu Mehr Demen...unclassified